Design Digital Twin Technology for Practicum Distance Learning - Hari Anna Lastya; Sadrina Sadrina; Muhammad Ikhsan; Fashbir Is (Postgraduate, University of Mataram, 2025)
One effective way to carry out laboratory practicums remotely is by using digital twin technology. This study investigates the feasibility and user response to using digital twin technology for remote Basic Electrical Energy practicums. This study employs a Research and Development (R&D) method involving students from the Department of Electrical Engineering. A validation sheet and a questionnaire were used to assess feasibility and user responses, respectively. The feasibility results of digital twin technology for remote practicums according to media experts obtained. The feasibility test achieved 90.71% from material experts and 91.43% from media experts from media experts, categorizing the system as